Role of metabolic reprogramming in pro-inflammatory cytokine secretion from LPS or silica-activated macrophages - Marrocco, Antonella; Ortiz, Luis A. (Frontiers in Immunology, 2022)
In the lungs, macrophages constitute the first line of defense against pathogens and foreign bodies and play a fundamental role in maintaining tissue homeostasis. Activated macrophages show altered immunometabolism and metabolic changes governing immune effector mechanisms, such as cytokine secretion characterizing their classic (M1) or alternative (M2) activation. Lipopolysaccharide (LPS)-stimulated macrophages demonstrate enhanced glycolysis, blocked succinate dehydrogenase (SDH), and increased secretion of interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α). Glycolysis suppression in LPS-stimulated macrophages inhibits IL-1β secretion, but not TNF-α, indicating metabolic pathway specificity that determines cytokine production. In contrast to LPS, the nature of the immunometabolic responses induced by non-organic particles, such as silica, in macrophages, its contribution to cytokine specification, and disease pathogenesis are not well understood. Silica-stimulated macrophages activate pattern recognition receptors (PRRs) and NLRP3 inflammasome and release IL-1β, TNF-α, and interferons, which are the key mediators of silicosis pathogenesis. In contrast to bacteria, silica particles cannot be degraded, and the persistent macrophage activation results in an increased NADPH oxidase (Phox) activation and mitochondrial reactive oxygen species (ROS) production, ultimately leading to macrophage death and release of silica particles that perpetuate inflammation. In this manuscript, we reviewed the effects of silica on macrophage mitochondrial respiration and central carbon metabolism determining cytokine specification responsible for the sustained inflammatory responses in the lungs.